LINGUAL FORM OF GARDEN NAMES AT RANOYAPO: Bentuk Lingual Nama-Nama Kebun di Ranoyapo - Vivi Nansy Tumuju; Vany Kamu; Donald R. Lotulung; James Edward Lalira (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research aims to find out the lingual forms and cultural meanings that appear in place naming and is studied based on the formation process, use, characteristics, and also the history of the Tontemboan language form, the local language spoken in Ranoyapo sub-district which is used as the research location. Place naming refers to the study of anthropological linguistics, which studies language and history. This research is qualitative and uses a descriptive approach. In the field of linguistics, this method is used by researchers to find out about many things related to society through language and its terminology. In collecting the data, the researcher used the method of simak and cakap from Mahsun (2007), with the aim of collecting data in the form of lingual forms and the phenomenon of naming places that appear in an utterance. Meanwhile, the commensurate and distributional methods were used to analyse the lingual form data to its smallest level. Based on the results of the research, root words dominate place naming besides being caused by affixation, reduplication, and composition. For example: Danda' [dandaɂ] 'name of the creek', Sukuyon [sukuyon] 'name of the creek', Kayong [kayoŋ] 'name of the creek', Sasano [sasano] 'name of the creek', Gawayas [gawayas] 'guava tree', Pahlawan [hero] 'hero', pa'boseng [paɂboseŋ] 'name of the creek', Ma'tenem [maɂtenəm] 'drying'. Land names with the lingual forms above are location identities in which there are aspects of domination such as water, plants, people, land, objects, stones, and animals.